Aggressive Angiomyxoma of the Bladder Neck Requiring Local Excision and Mitrofanoff Formation - M. Davari; B. W. Lamb; S. Chowdhury; C. Jameson; J. D. Kelly; T. Greenwell (Case Reports in Urology)
Aggressive angiomyxoma is a rare mesenchymal tumour predominantly affecting the female pelvis and perineum but has also been described in males. This tumour can often present a diagnostic challenge and has a propensity for local recurrence after surgical excision. We present an unusual case of aggressive angiomyxoma arising from the bladder of a female patient which required local excision and Mitrofanoff formation.